Optimization of Laboratory Quality Management in Improving Student Competence - Dina Rahmawati; Zulkhairi, Zulkhairi; Fitriyani; Safriadi; Muhammad Ali Akbar; Rosadi, Muhamad (Jurnal Pendidikan IPA Indonesia, 2024)
This aims to analyze and examine laboratory quality management in enhancing student competencies. The research method used is qualitative, specifically a case study approach. The subjects of the study include school principals, laboratory heads, lab technicians, teachers, and students. Data collection was conducted through observations, interviews, literature studies, and documentation analysis. The instruments utilized in this research are observation sheets, interview guidelines, and field notes. The results from both schools indicated that the planning for laboratory quality management was prepared at the beginning of the new academic year, which included annual and semester programs, equipment procurement, and inventory management. The implementation of laboratory quality management involved conducting practical work as scheduled, with facilities used optimally. Monitoring and evaluation of laboratory quality management included regular assessments through observations and interviews with teachers and students to identify any shortcomings. Follow-up actions for laboratory quality management included corrective actions taken based on evaluation results, such as facility improvements and the addition of equipment. Barriers to laboratory quality management included equipment maintenance. Solutions to overcome these barriers involved facility improvements, equipment additions, additional training for staff, increased involvement of lab technicians, and optimizing funding. It was concluded that the series of laboratory quality management within the PDCA framework functioned effectively, commencing with planning, implementation, monitoring and evaluation, and follow-up. The management of the Biology laboratory can optimize the competencies of students at SMA Negeri 1 Ciamis and SMA Negeri 1 Pangandaran.